2009
DOI: 10.1063/1.3057356
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the background toroidal rotation on particle and heat turbulent transport in tokamak plasmas

Abstract: Recent developments in the gyrokinetic theory have shown that, in a toroidal device, the Coriolis drift associated with the background plasma rotation significantly affects the small scale instabilities ͓A. G. Peeters et al., Phys. Rev. Lett. 98, 265003 ͑2007͔͒. The later study, which focuses on the effect of the Coriolis drift on toroidal momentum transport is extended in the present paper to heat and particle transport. It is shown numerically using the gyrokinetic flux-tube code GKW ͓A. G. Peeters and D. St… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
136
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 88 publications
(141 citation statements)
references
References 25 publications
(25 reference statements)
5
136
0
Order By: Relevance
“…Also, the effect of rotation, which is one of the mechanisms that causes poloidal asymmetry, has not been taken into account. Fluid and gyrokinetic modeling of rotation induced contributions to the transport fluxes, 19,20 have shown that in the ITG-dominated case, the centrifugal force leads to higher inward convection for impurities ͑increasing with impurity mass͒. This agrees with the predictions of the present work, since the strength of the asymmetry increases with Z, and accumulation at the outboard side should lead to an increased inward flux.…”
Section: -3supporting
confidence: 82%
“…Also, the effect of rotation, which is one of the mechanisms that causes poloidal asymmetry, has not been taken into account. Fluid and gyrokinetic modeling of rotation induced contributions to the transport fluxes, 19,20 have shown that in the ITG-dominated case, the centrifugal force leads to higher inward convection for impurities ͑increasing with impurity mass͒. This agrees with the predictions of the present work, since the strength of the asymmetry increases with Z, and accumulation at the outboard side should lead to an increased inward flux.…”
Section: -3supporting
confidence: 82%
“…The term containing U ef f is the only O(ρ 0 * ) term in equation (8). The O(ρ * ) and higher terms have been assembled in the right-hand-side: by definition, γ is such that…”
Section: Physical Meaning Of the Velocity Determined By The Cctd Methodsmentioning
confidence: 99%
“…However, both theoretical and experimental works of the past two decades [2][3][4][5][6][7][8][9][10][11][12][13][14][15] suggest that sheared E × B flows can moderate such anomalous transport and hence improve the performance of magnetically confined fusion plasmas.…”
Section: Introductionmentioning
confidence: 99%
“…In this paper, particular interest is given to impurity (more specifically on roto-diffusion [17]) and momentum transport as they both rely on parallel symmetry breaking [12,17,18]. To this end the neoclassical first order distribution function is needed for impurities as well as for the main ions.…”
Section: A Analytical First Order Neoclassical Distribution Functionmentioning
confidence: 99%
“…The impact of the neoclassical equilibrium on turbulent momentum transport has been explored in details in [12][13][14][15][16] and found to be significant compared to other sources of momentum flux [16] such as the Coriolis drift and the flux surface up-down asymmetry. Turbulent momentum and impurity transport being not completely disconnected, in particular with respect to the role of symmetry breaking mechanisms [17,18], these results motivated a study of the impact of the neoclassical equilibrium distribution function on turbulent impurity transport. To this end, two approaches are adopted: the derivation of a fluid model including this correction and numerical simulations using the coupled codes NEO [19,20] and GKW [22].…”
Section: Introductionmentioning
confidence: 99%